Sosialisasi Sistem Peyimpanan Rekam Medis Berdasarkan Standar Akreditasi Puskesmas Medan Johor Tahun 2021 - Angelia Putriana; Erlindai Purba (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Health center accreditation standards are one of the assessments of the medical record file storage system. The medical record file storage system at the Medan Johor Health Center is very important because it helps officers in retrieving and returning files on the medical record file storage rack. The socialization of the medical record file storage system based on this accreditation standard was carried out at the Medan Johor Health Center as a form of updating knowledge and implementing standardized medical record file storage. The purpose of this community service is to help the Medan Johor Health Center in preparing all the files and necessities to follow the Second Edition of the Public Health Center accreditation standard, version 2021 regarding the medical record file storage system at the Medan Johor Health Center. This community service method is to provide socialization of the medical record file storage system in accordance with the second edition of the Puskesmas accreditation instrument, version 2021. The results of community service are expected that medical record officers are able to apply procedures for retrieval and return of medical record files according to the accreditation standards of the storage system which will help medical record officer in the future when the accreditation period for the Medan Johor Health Center will arrive